Transcriptome analysis of Lr19-virulent mutants provides clues for the AvrLr19 of Puccinia triticina - Cui, Zhongchi; Wu, Wenyue; Fan, Fan; Wang, Fei; Liu, Daqun; Di, Dianping; Wang, Haiyan (Frontiers in Microbiology, 2023)
Wheat leaf rust caused by Puccinia triticina (Pt) remains one of the most destructive diseases of common wheat worldwide. Understanding the pathogenicity mechanisms of Pt is important to control wheat leaf rust. In this study, the urediniospores of Pt race PHNT (wheat leaf rust resistance gene Lr19-avirulent isolate) were mutagenized with ethyl methanesulfonate (EMS), and two Lr19-virulent mutants named M1 and M2 were isolated. RNA sequencing was performed on samples collected from wheat cultivars Chinese Spring and TcLr19 infected with wild-type (WT) PHNT, M1, and M2 isolates at 14 days post-inoculation (dpi), respectively. 560 genes with single nucleotide polymorphisms (SNPs) and insertions or deletions (Indels) from non-differentially expressed genes were identified. Among them, 10 secreted proteins were screened based on their fragments per kilobase of exon model per million mapped reads (FPKM) values in the database. Quantitative reverse transcription PCR (qPCR) results showed that the expression profiles of 7 secreted proteins including PTTG_27471, PTTG_12441, PTTG_28324, PTTG_26499, PTTG_06910, PTTG_26516, and PTTG_03570 among 10 secreted proteins in mutants were significantly different with that in wild-type isolate after infection wheat TcLr19 and might be related to the recognition between Lr19 and AvrLr19. In addition, a total of 216 differentially expressed genes (DEGs) were obtained from three different sample comparisons including M1-vs-WT, M2-vs-WT, and M1-vs-M2. Among 216 DEGs, 15 were predicted to be secreted proteins. One secreted protein named PTTG_04779 could inhibit programmed progress of cell death (PCD) induced by apoptosis-controlling genes B-cell lymphoma-2 associated X protein (BAX) on Nicotiana benthamiana, indicating that it might play a virulence function in plant. Taken together, total 8 secreted proteins, PTTG_04779, PTTG_27471, PTTG_12441, PTTG_28324, PTTG_26499, PTTG_06910, PTTG_26516, PTTG_03570 are identified as AvrLr19 candidates. Our results showed that a large number of genes participate in the interaction between Pt and TcLr19, which will provide valuable resources for the identification of AvrLr19 candidates and pathogenesis-related genes.